Editorial (KEMANUSIAAN The Asian Journal of Humanities, 2024)
This first issue of Volume 23 of KEMANUSIAAN the Asian Journal of Humanities (KAJH) is the first themed issue published by this journal and is dedicated to historian Abdul Rahman Haji Ismail, the founding editor of the journal. Originally titled Jurnal Kemanusiaan (Journal of Humanities), the first volume was published over two decades ago in 1994. Befitting the dedication to a historian, the current issue features five articles that examine regional as well as universal issues in history.